THE MOTIVE OF ATTITUDE ALTERATION TO PURSUE SELF-ACTUALIZATION IN THE NOVEL THE SECRET GARDEN BY FRANCES HODGSON BURNETT - Az-Zahra, Sasha; Prautomo, Adi (Prologue: Journal on Language and Literature, 2026)
The researcher analyzes the motive of attitude alteration to pursue self-actualization in the novel The Secret Garden by Frances Hodgson Burnett. It aims to find the forms of attitude alteration found in the novel, and to analyze the motive of attitude alteration in pursuit of self-actualization in the novel. This research uses Burrhus Frederic Skinner’s operant conditioning theory to find the forms of attitude alteration and Abraham Maslow’s hierarchy of needs theory to analyze changes in attitude towards self-actualization. This research uses a qualitative method with a descriptive approach for a close reading to analyze the novel’s narrative and character dialogues. The findings of this study revealed four forms of attitude alteration: positive reinforcement, negative reinforcement, positive punishment, and negative punishment. Each form significantly influences how characters strive to meet their needs in various circumstances, ultimately leading to personal fulfillment. The results shows that positive reinforcement most often influences characters, enabling individuals to reach the stage of self-actualization more frequently. This research demonstrates that the adoption of positive attitudes empowers characters to achieve their goals and improves their ability to engage in social interactions.